Immersion, Absorption, and Spiritual Experience: Some Preliminary Findings - Glicksohn, Joseph; Ben-Soussan, Tal Dotan (Frontiers in Psychology, 2020)
Many traditions have utilized silent environments to induce altered states of consciousness and spiritual experiences. Neurocognitive explorations of spiritual experience can aid in understanding the underlying mechanism, but these are surprisingly rare. We present the verbal report and the EEG alpha profile of a female participant scoring a maximal 34 on the Absorption Scale, recorded before and while she was immersed in a whole-body perceptual deprivation (WBPD) tank. We analyze her trancelike experience in terms of the imagery reported: a spaceship, corridors, doors, a man dressed in white, speaking to God, the sun, supernova, concentric images, and an out-of-the-body experience. Her report is indicative of a spiritual experience, given that she felt that she was ‘meeting God’ in the lab. She exhibited both frontal and parietal left > right alpha power asymmetry at baseline; while in the WBPD condition, there was a global increase in alpha power, and especially a sharp increase in right-frontal alpha power. Her verbal report and EEG alpha profile is compared to those of another female participant, also scoring high on absorption, whose verbal report was also indicative of a trancelike experience. For further comparison, we present the data for two participants scoring low on absorption. Spiritual experience that can be verbalized might be associated with a marked increase in right-frontal alpha power, as reported here. In contrast, a mystical experience characterized by ineffability would be indicated by a marked increase in left-frontal alpha power.